Is There a Preoperative Morphine Equianalgesic Dose that Predicts Ability to Achieve a Clinically Meaningful Improvement Following Spine Surgery?. Issue 2 (25th July 2017) - Wick, Joseph B; Sivaganesan, Ahilan; Chotai, Silky; Archer, Kristin R; Posey, Samuel L; Evans, Parker T; Campbell, Joel R; Devin, Clinton J
Abstract: BACKGROUND: Preoperative opioid use is widespread and associated with worse patient-reported outcomes following spine surgery. OBJECTIVE: To calculate a threshold preoperative morphine equianalgesic (MEA) dose beyond which patients are less likely to achieve the minimum clinically important difference (MCID) following elective surgery for degenerative spine disease. METHODS: The study included 543 cervical and 1293 lumbar patients. Neck Disability Index and Oswestry Disability Index scores were collected at baseline and 12 mo postoperatively. Preoperative MEA doses were calculated retrospectively. Multivariate logistic regression was then performed to determine the relationship between MEA dose and the odds of achieving MCID. As a part of this regression, Bayesian inference and Markov Chain Monte Carlo methods were used to estimate the values of inflection points (or "thresholds") in MEA. RESULTS: Overall, 1020 (55.5%) patients used preoperative opioids. A total of 50.3% of cervical and 61.9% of lumbar patients achieved MCID. The final logistic regression model demonstrated that MCID achievement decreased significantly when mean preoperative MEA dose exceeded 47.8 mg/d, with a 95% credible interval of 29.0 to 60.0 mg/d. CONCLUSION: Minimum and maximum MEA doses exist, between which increasing opioid dose is associated with decreased ability to achieve clinically meaningful improvement following spine surgery. Patients with preoperative MEA dose exceeding 29 mg/d, the lower limit of the 95% credible interval for the mean MEA dose above which patients exhibit significantly decreased achievement of MCID, may be considered for preoperative opioid weaning.